Estimating environmental flow requirements downstream of the Chara Chara weir on the Blue Nile River - McCartney, Matthew P.; Shiferaw, A.; Seleshi, Y. (2008)
Over the last decade flow in the Abay River (i.e., the Blue Nile) has been modified by operation of the Chara Chara weir and diversions to the Tis Abay hydropower stations, located downstream of the rivers source, Lake Tana. The most conspicuous impact of these human interventions has been significantly reduced flows over the Tis Issat Falls. This paper presents the findings of a hydrological study conducted to estimate environmental flow requirements downstream of the weir. The South African desktop reserve model was used to determine both high and low flow requirements in the reach containing the Falls. The results indicate that to maintain the basic ecological functioning in this reach requires an average annual allocation of 862 Mm3 (i.e. equivalent to 22% of the mean annual flow). Under natural conditions there was considerable seasonal variation, but the absolute minimum mean monthly allocation, even in dry years, should not be less than approximately 10 Mm3 (i.e. 3.7 m3s-1). These estimates make no allowance for maintaining the aesthetic quality of the Falls, which are popular with tourists. The study demonstrated that, in the absence of ecological information, hydrological indices can be used to provide a first estimate of environmental water requirements. However, to ensure proper management, much greater understanding of the relationships between flow and the ecological condition of the riverine ecosystem is needed.